Position of the Proximal Manica Flexoria under different grades of fetlock joint extension – A biomechanical observational study in the equine fore- and hindlimb - Schweinsberg, Lorenz P.; Ehrle, Anna; Jensen, Katharina Charlotte; Lischer, Christoph J.; Cender, Andrea Noguera (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The aim of this study was to examine the position of the proximal manica flexoria and the proximal scutum under different grades of fetlock joint extension and to describe measurements and compare findings between equine fore- and hindlimbs.Study Design It was an observational study.Results During fetlock joint extension, the proximal manica flexoria and the proximal scutum displace distally relative to the palmar/plantar extent of the sagittal ridge of the cannon bone. The proximal manica flexoria is further displaced distal to the proximal scutum within the fetlock canal. No significant differences were identified between fore- and hindlimbs at different levels of fetlock joint extension. The proximal scutum was observed to be longer and thicker and the tendinous part of the manica flexoria was longer in forelimbs compared with hindlimbs.Conclusion and Clinical Relevance The described findings contribute to the understanding of the pathogenesis of manica flexoria tearing. The fact that the proximal scutum and the tendinous part of the manica flexoria are shorter in the hindlimb might explain why the manica flexoria is more likely to get caught on the proximal aspect of the scutum and develop a tear in the equine hindlimb.
Keywords: equine; fetlock joint; manica flexoria; scutum